Integrasi Sistem Informasi Kesehatan dan Jaringan Dukungan Teman Sebaya untuk Pencegahan Anemia pada Remaja: Literature Review - Khoufah, Lilik; Susmiati, Susmiati; Winarti, Eko (Jurnal Ners, 2025)
Anemia remains a major nutritional problem among global adolescents with prevalence reaching 32% in adolescent girls and 12% in adolescent boys. Traditional anemia prevention approaches face challenges of low compliance and limited reach, while adolescents as digital natives are more responsive to technology-based interventions and peer support. Objective: To synthesize articles on the integration of health information systems and peer support networks in adolescent anemia prevention to identify effective and sustainable models. Narrative literature review of English-language articles (January 2014-June 2025) from PubMed/MEDLINE, Scopus, and Web of Science databases. Inclusion criteria encompassed studies on adolescents (10-19 years) addressing anemia prevention through health information systems and/or peer counseling. Thematic analysis was conducted to identify effective integration patterns. Nine articles demonstrated that digital interventions through mobile applications and platforms like WhatsApp significantly improved adolescents’ knowledge, iron supplementation compliance, and hemoglobin levels. Peer support proved effective in reducing anemia prevalence through direct supervision and community-based education. Integrative models combined technological advantages in accessibility with social network strengths in driving behavioral change. Integration of digital health information systems with peer support networks provides significant positive impact in adolescent anemia prevention. This approach offers innovative solutions that address limitations of conventional interventions by leveraging adolescents’ communication preferences and social dynamics. Keywords: adolescent anemia, health information systems, peer support, mHealth, anemia prevention